Strongly almost lacunary I-convergent sequences - Kilicman, Adem; Borgohain, Stuti (Hindawi Publishing Corporation, 2013)
We study some new strongly almost lacunary I-convergent generalized difference sequence spaces defined by an Orlicz function. We give also some inclusion relations related to these sequence spaces.